PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN DENGAN OPINI AUDIT SEBAGAI PEMODERASI (Studi empiris pada perusahaan manufaktur yang terdaftar di BEI periode 2014-2017) - Lyara Yashinta; Anisma Yuneita; S Adri Satriawan R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to prove the influence Of Profitability, Firm Size, andFirm Age on Timeliness of Financial Reporting with Audit Opinion as themoderating. The population in this study are all companies listed on the StockExchange in 2014 – 2017. Samples were companies listed on the Indonesia StockExchange (IDX), which is engaged in manufacturing. Samples taken as many as66 manufacturing companies, determined by purposive sampling method. Datawas collected using non-participant observation. Analysis technique used is theLogistic Regression Analysis by using Moderated Regression Analysis. The typeof data in this research are secondary data from the audited financial statementsof companies listed on the Indonesia Stock Exchange (IDX) in the year 2014-2017and report the performance of companies listed on the Stock Exchange . The datais sourced from www.idx.co.id. The results of this study are 1. There is effect ofprofitability on the timeliness of financial reporting in companies. 2. There arefirm size influence the timeliness of financial reporting in companie. 3. There arefirm age influence the timeliness of financial reporting in companie. 4. Auditopinion is able to moderate the influence of profitability on the timeliness offinancial reporting. 5. Audit opinion is able to moderate the influence of firm sizeon the timeliness of financial reporting. 6. Audit opinion is able to moderate theinfluence of firm age on the timeliness of financial reporting.Keywords : Profitability, Firm Size, Firm Age, Audit Opinion, Timeliness ofFinancial Reporting.